Overexpression of the ped/pea-15 Gene Causes Diabetes by Impairing Glucose-Stimulated Insulin Secretion in Addition to Insulin Action - Vigliotta, Giovanni (American Society for Microbiology, 2004)
Overexpression of the ped/pea-15 gene is a common feature of type 2 diabetes. In the present work, we show that transgenic mice ubiquitously overexpressing ped/pea-15 exhibited mildly elevated random-fed blood glucose levels and decreased glucose tolerance. Treatment with a 60% fat diet led ped/pea-15 transgenic mice to develop diabetes. Consistent with insulin resistance in these mice, insulin administration reduced glucose levels by only 35% after 45 min, compared to 70% in control mice. In vivo, insulin-stimulated glucose uptake was decreased by almost 50% in fat and muscle tissues of the ped/pea-15 transgenic mice, accompanied by protein kinase Cα activation and block of insulin induction of protein kinase Cζ. These changes persisted in isolated adipocytes from the transgenic mice and were rescued by the protein kinase C inhibitor bisindolylmaleimide. In addition to insulin resistance, ped/pea-15 transgenic mice showed a 70% reduction in insulin response to glucose loading. Stable overexpression of ped/pea-15 in the glucose-responsive MIN6 beta-cell line also caused protein kinase Cα activation and a marked decline in glucose-stimulated insulin secretion. Antisense block of endogenous ped/pea-15 increased glucose sensitivity by 2.5-fold in these cells. Thus, in vivo, overexpression of ped/pea-15 may lead to diabetes by impairing insulin secretion in addition to insulin action.